Claire Clifton & Martina Nicolls: Edible Gifts - D., J.M. (Petits Propos Culinaires, 2025)
Claire Clifton & Martina Nicolls: Edible Gifts: Bodley Head, London, 1982: 96 pp., hardback, colour illustrations, £4.95.